The feasibility of a cold storage facility for fish in Aceh during the COVID-19 pandemic. Issue 1 (February 2021) - Fahlevi, H; Chan, S; Hasibuan, P; Fadli, N; Edhy Sofyan, S; Rianjuanda; Syukri, M; Saidi, T; Dawood, R
Abstract: The majority of catches by fishermen in Aceh, Indonesia are sold raw, directly to consumers, and in the local market. This contributes to the low price of fish and low income for the fishermen, and the COVID-19 outbreak has made this situation even worse. One solution could be the establishment of a cold storage business in the area. This study assessed the financial feasibility of a 200-ton cold storage business in Banda Aceh, the capital of Aceh province. Using secondary data collected from online sources, we applied the most common financial indicators used in feasibility studies, namely Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit-Cost Ratio (BCR). A sensitivity test was also performed to predict the feasibility of the cold storage business if the basic assumptions are changed. We found that cold storage in Banda Aceh is financially feasible as the NPV was positive, the IRR was higher than the interest rate (i.e., the discount rate), and the BCR was higher than 1. Besides, the sensitivity test also suggested that cold storage would still be feasible even if there were a 20% increase or decrease in storage capacity and project costs.